Narrow syntax and phonological form : scrambling in the Germanic languages - Chocano, Gema (Linguistik aktuell, 2007)
'Scrambling', the kind of word order variation found in West Germanic languages, has been commonly treated as a phenomenon completely unrelated to North Germanic 'Object Shift'. This book questions this view and defends a unified analysis on the basis of strictly syntactic and phonological evidence. Given that its main conclusions are drawn from German data, it also sheds light on several problematic aspects of the grammar of this language, which have traditionally resisted a principled account. Prominent among these are: the inconsistent behaviour of German coherent infinitives with respect t.